EXPANSIN A1-mediated radial swelling of pericycle cells positions anticlinal cell divisions during lateral root initiation - Ramakrishna, Priya; Ruiz Duarte, Paola; Rance, Graham A.; Schubert, Martin; Vodermaier, Vera; Vu, Lam Dai; Murphy, Evan; Vilches-Barro, Amaya; Swarup, Kamal; Moirangthem, Kamaljit; Jørgensen, Bodil; Cotte, Brigitte van de; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2019)
In plants, postembryonic formation of new organs helps shape the adult organism. This requires the tight regulation of when and where a new organ is formed and a coordination of the underlying cell divisions. To build a root system, new lateral roots are continuously developing, and this process requires the tight coordination of asymmetric cell division in adjacent pericycle cells. We identified EXPANSIN A1 (EXPA1) as a cell wall modifying enzyme controlling the divisions marking lateral root initiation. Loss of EXPA1 leads to defects in the first asymmetric pericycle cell divisions and the radial swelling of the pericycle during auxin-driven lateral root formation. We conclude that a localized radial expansion of adjacent pericycle cells is required to position the asymmetric cell divisions and generate a core of small daughter cells, which is a prerequisite for lateral root organogenesis.